(untitled) (Research, Society and Development, 2021)
Social discrimination is something that is recurrent in Brazilian society, thus causing a great inequality in relation to the most disadvantaged and marginalized groups, from the past times. In light of this, this article analyzes affirmative actions in Brazil and their applicability, as a means of demonstrating the importance of this institute in combating inequalities so deeply rooted socially. With this, the historical evolution and the concept of affirmative actions will be approached, especially in the Brazilian context. Then, the fundamental principle and right of equality will be emphasized, as well as the admission of the affirmative action institute by the 1988 Federal Constitution. Finally, it will also be attributed which position adopted by the Supreme Federal Court on the subject. For that, the method adopted is the deductive one, using historical, doctrinal, jurisprudential and articles referring to the content approach. As outstanding results, it is noteworthy that affirmative actions are supported by the Federal Constitution, as a way of guaranteeing equality.